Relay Selection-and-Jamming Scheme with Nonlinear Energy Harvesting. (11th October 2021) - Pham-Minh, Triet; Ho-Van, Khuong; Nguyen-Minh, Hoa; Nghi-Vinh, Khanh
Abstract : When direct source-destination communications are in outage, relay selection is a preferable solution to improve reliability for this communications. However, such a relay selection makes the eavesdropper better overhear source data through both source-relay and relay-destination communication hops, losing data security. To improve both reliability and security, this paper proposes a relay selection-and-jamming (RaJ) scheme to select one intermediate node as a conventional relay and another node as a jammer. To enhance energy efficiency, all intermediate nodes harvest radio frequency energy in source signals for their operations with nonlinear energy harvesting (NL-EH). The security and reliability of the RaJ scheme are assessed through suggested rigorous/asymptotic expressions and are significantly better than two benchmark schemes without neither jamming nor both relay selection and jamming. Additionally, they can be optimized with reasonable selection of specifications. Moreover, the NL property of the energy harvesters dramatically affects the reliability but negligibly degrades the security for the RaJ scheme. Furthermore, the linear EH (L-EH) is more reliable but less secure than the NL-EH.